(untitled) (Medico Legal Update, 2020)
Objective: To determine the effectiveness of an educational program on nurses’ knowledge toward burn management and To identify the relationship between nurses’ knowledge toward burn management and their socio-demographic data. Methodology: ‘’quasi-experimental’’ loaded out to accomplish the golas of the study consisting of (40) nurses at specialized burn center in Al-Najaf City/Al-Najaf Al-Ashraf Health Directorate from October 6th, 2019 to August 23nd, 2020. Results: the study show that there are highly significant differences in the nurses ’knowledge between the study and control groups in the post-test and the program was positive for the nurses ’knowledge about burn care and that there was a good improvement in the nurses’ knowledge between pre and post test.